The moderating effect of generational characteristics on the relationship between psychological capital and job performance: the development of conceptual framework / Zuraidah Sipon, Muhammad Majid and Norshahniza Sahari - Sipon, Zuraidah; Majid, Muhammad; Sahari, Norshahniza (UiTM Cawangan Johor, 2024)
Employee job performance plays a pivotal role in ascertaining an organisation's competitive edge. Despite the recent surge in interest in Psychological Capital (PsyCap) as a novel approach to augmenting employee job performance, this area of study has received limited attention in the Malaysian context. Meanwhile, the issue of stress and anxiety appears to be closely associated with Generation Z (Gen Z). As the youngest cohort in the workforce, the initial phase of Gen Z's entry into the workplace gives rise to various concerns, including job engagement and job turnover. Despite extensive discussions on these matters in recent studies, the understanding of their impact on job performance and the underlying mechanisms remains limited. Hence, this conceptual paper aims to propose a conceptual model that empirically examines the relationship between PsyCap and job performance. Additionally, the role of generational characteristics as a moderator in this relationship will also be explored. The proposed conceptual framework holds significant potential for contributing to future research endeavours.